Pengaruh Ukuran Perusahaan, Profitabilitas, Capital Intensity, dan Corporate Governance Terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Sub Sektor Energi yang Terdaftar di Bursa Efek Indonesia Secara Berturut-Turut Tahun 2019-2023 - Ammar Alamsyah; Banu Witono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to test and analyze the effect of company size, profitability, capital intensity, and corporate governance on tax aggressiveness. Corporate governance in this study is proxied by the size of the board of directors, audit committee, and independent commissioners. This research uses quantitative methods with secondary data obtained from the annual financial statements of energy sub sector companies listed on the Indonesia Stock Exchange (IDX) consecutively from 2019 - 2023. The sampling method used was purposive sampling, with a total 102 observation data from 21 companies. Data analysis was carried out using multiple linear regression. The results showed that profitability, capital intensity had a significant effect on tax aggressiveness. Meanwhile, company size and corporate governance variable proxied by the size of the board of directors, audit committee, and independent commissioners showed no significant effect on tax aggressiveness.